Muscle Mass and Quality of Life of Elderly People in Panti Tresna Werdha in Bandung - Lambok K. K. Stein; Siska Wiramihardja; Iceu D. Kulsum (Journal of Medicine and Health, 2018)
The proportion of elderly continues to increase from year to year due to theincrease of life expectancy. Elderly will experience degenerative process related tomuscle mass. This can disrupt the quality of life. The aim of this study was to determinethe muscle mass and quality of life (QoL) in the elderly. This study used cross sectionalapproach with the number of subjects as many as 32 elderly residents of Tresna Werdhain Bandung. The tool used to measure muscle mass is BIA Tanita SC-240 while theinstrument used in measuring quality of life is the WHOQL-BREF questionnaire. Theresult showed that the mean value of muscle mass per unit body surface area was 22.86±2.20 kg/m 2 . The highest average value of QoL is the physical domain (59.15±8,06%)while the lowest is the environmental domain (42.97±11.11%). The conclusion of thisstudy is muscle mass possessed by elderly study participants is good. The QoL isclassified as moderate.Keywords: elderly people, muscle mass, quality of life,  WHOQL-BREF questionnaire